A Lexical Representational Mechanism Underlying Verbal Satiation: An Empirical Study With Rarely Used Chinese Characters - Cao, Kang; Li, Jie; Wu, Baizhou; Zhang, Hong; He, Hu (Frontiers in Psychology, 2019)
High repetitions of a character induce a feeling of uncertainty of the character. This phenomenon is named as Verbal Satiation. However, the locus and nature of the verbal satiation remain controversial. To investigate whether verbal satiation occurs at the lexical representational locus, we used rarely-used Chinese characters as stimuli to exclude confounding factor of meaning access. Participants were asked to judge whether or not a single Chinese character such as “山” is a composition of a rarely-used Chinese character such as “峠”. The experiment consists of 4 sets with 11 blocks in each set. Every 20 trials consist of a block, and the same rarely-used characters were repeated in half of these trials. To observe the satiation effect that is offset by practice effect with more statistical power, we did ANOVA analysis for each set. The statistical results revealed that subjects responded differently at different time periods. In the first set, participants responded faster in later trials; After that, reversely, participants responded slower in later trials; Then they responded slower for the repeated characters in middle trials; Finally, participants responded slower for the repeated characters without regard to the trial position. These results show a competition process between satiation effect and practice effect and reveal that the verbal satiation can occur at a lexical representational locus.